2017
DOI: 10.1097/tp.0000000000001679
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effect of Apyrase Treatment and hCD39 Overexpression on Chronic Renal Fibrosis After Ischemia-Reperfusion Injury

Abstract: A single dose of apyrase administration before IRI protects from both acute and chronic renal injuries and may have clinical application in protection from ischemic-induced renal injury. Furthermore, transgenic expression of hCD39 is associated with increased renal fibrosis after ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Acute kidney injury (AKI) is a prominent risk factor for the development of CKD [8]. In recent years, ischemia-induced AKI have attracted much attention because of high rate of later renal fibrosis [9,10]. However, the related specific mechanism have not been rigorously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a prominent risk factor for the development of CKD [8]. In recent years, ischemia-induced AKI have attracted much attention because of high rate of later renal fibrosis [9,10]. However, the related specific mechanism have not been rigorously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Lung fibrosis (Wang et al, 2009) Lentiviral depletion; rat silicosis model Activation of L-TGF-β1; production of hydroxyproline and ECM Profibrotic CD39 Chronic renal Fibrosis (Roberts et al, 2017) CD39 over-expressing transgenic mice…”
Section: Profibroticmentioning
confidence: 99%
“…However, the role of CD39 protein per se in fibrotic diseases have been studied and showed competing results. On one hand, CD39 hyperfunction caused the accumulation of extracellular ADO and facilitated the activation of ADO signaling pathway, resulting in tissue fibrosis (Roberts et al, 2017). In renal ischemia-reperfusion injury models, overexpression of CD39 in the transgenic mice showed significantly more severe renal fibrosis via upregulating ADO and stimulating profibrotic downstream pathways through interaction with adenosine A2B receptors (Roberts et al, 2017).…”
Section: Adenosine Generation Profibroticmentioning
confidence: 99%
See 1 more Smart Citation
“…Koo et al demonstrated that a P2X7 receptor antagonist (or P2X7 receptor deficiency in hematopoietic cells) ameliorates murine renal IRI by expansion of regulatory T (Treg) cells. Similarly, apyrase treatment to degrade extracellular ATP protected mice from both acute and chronic renal IRI …”
Section: Targeting Atp In Iri and Graft Preservationmentioning
confidence: 99%